UV SPECTROPHOTOMETRIC STUDY OF AMOXICILLIN–ANTACIDS INTERACTION AND ESTIMATION OF ANTIMICROBIAL ACTIVITY - Islam, Md. Shahidul; Mojumder, Tanjum Jahan (Universal Journal of Pharmaceutical Research, 2023)
Background and aims: Interaction between a drug and another element which causes a drug interaction when it prevents the medication from functioning as intended. Usually, an interaction can change how the drug is absorbed, distributed, metabolized and eliminated by the body. The purpose of this study is to assess the type and strength of in-vitro complexation that may be caused by an interaction between Amoxicillin with Antacids and investigation of antimicrobial study of Amoxicillin. Methodology: This work ensures as a possible interaction between Amoxicillin with Mg(OH)₂ (Antacid-1) and CaCO₃ (Antacid-2) which was determined by Job’s plot approach. Investigating the number of Mg(OH)₂ (Antacid-1) and CaCO₃ (Antacid-2) connected in the complexation with Amoxicillin complexes was demonstrated by exploiting several spectrophotometric methods. Ultraviolet studies of these were carried out and balanced. The microbial sensitivity assessment is important to identify whether Amoxicillin’s efficacy has changed as a result of its interaction with antacids. Findings: The study supported that there is a probable interaction between Amoxicillin with antacids which is confirmed by job’s plot method. The Amoxicillin absorbance is verily different from absorbance of Amoxicillin –Mg(OH)₂ (Antacid-1) and Amoxicillin- CaCO₃ (Antacid-2). And the intensity of the peak of Amoxicillin changes particularly when Amoxicillin forms strong 1:1 complex with Mg(OH)₂ (Antacid-1) and CaCO₃ (Antacid-2). These curves were able to indicate strong kinetics of complexation of Amoxicillin with antacids. By Antimicrobial investigation against gram positive bacteria, it was certain that the zone of inhibition of Amoxicillin with Mg(OH)₂ (Antacid-1) and CaCO₃ (Antacid-2) reduced from 15 mm, 11 mm and 9 mm respectively against gram positive bacteria and Amoxicillin with Mg(OH)₂ and CaCO₃ did not exhibit any detectable antibacterial action when tested against gram negative bacteria. Conclusion: It has been demonstrated that the standard absorbance of Amoxicillin differs significantly from the absorbance of drug-antacid and the antimicrobial activity is also reduced due to interaction. Peer Review History: Received: 5 December 2022; Revised: 9 January; Accepted: 23 February 2023; Available online: 15 March 2023 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewers: Dr. Nicola Micale, University of Messina, Italy, nmicale@unime.it Dr. Hayriye Eda Şatana Kara, Gazi University, Turkey, eda@gazi.edu.tr